Performance Benefits From Providing Assistance in Networks: Relationships That Generate Learning. (February 2018) - Shah, Neha Parikh; Cross, Rob; Levin, Daniel Z.
Social network scholarship emphasizes that receiving resources from others in a network can benefit an individual's job performance. Yet this paradigm rarely considers the effects on the provider of assistance. Outside the networks literature, scholars have been increasingly attentive to factors that affect motivations to provide help (i.e., prosocial motivation). However, the performance effects associated with providing help have been mixed. We concentrate specifically upon assistance that has the potential to enhance the providers' learning and knowledge base and, hence, their performance. Using a bounded-network survey in a large consulting firm, we show that providing problem-solving assistance to many others on task-related matters increases the provider's own work performance. We then consider how this learning may be affected by other relational and contextual factors. In so doing, we shift the predominant network perspective that people accrue performance advantages from receiving assistance to show that such advantages also occur—under the right circumstances—from providing it.